Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Discover detailed solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Sure, let's solve the equation step by step:
[tex]\[ \frac{3t - 2}{4} - \frac{2t + 3}{3} = \frac{2}{3} - t \][/tex]
1. Eliminate the fractions by finding a common denominator, which in this case is 12 (the least common multiple of 4 and 3). Multiply every term by 12 to clear the fractions:
[tex]\[ 12 \left( \frac{3t - 2}{4} \right) - 12 \left( \frac{2t + 3}{3} \right) = 12 \left( \frac{2}{3} \right) - 12t \][/tex]
2. Simplify each term:
[tex]\[ 3t \cdot 3 - 2 \cdot 3 - 4 \cdot (2t + 3) = 4 \cdot 2 - 12t \][/tex]
[tex]\[ 9t - 6 - (8t + 12) = 8 - 12t \][/tex]
3. Distribute and Combine like terms:
[tex]\[ 9t - 6 - 8t - 12 = 8 - 12t \][/tex]
[tex]\[ t - 18 = 8 - 12t \][/tex]
4. Get all [tex]\( t \)[/tex]-terms on one side and the constants on the other side:
Add [tex]\( 12t \)[/tex] to both sides of the equation:
[tex]\[ t + 12t - 18 = 8 \][/tex]
Combine the [tex]\( t \)[/tex]-terms on the left-hand side:
[tex]\[ 13t - 18 = 8 \][/tex]
5. Solve for [tex]\( t \)[/tex]:
Add 18 to both sides:
[tex]\[ 13t = 26 \][/tex]
Divide both sides by 13:
[tex]\[ t = 2 \][/tex]
Thus, the solution to the equation is:
[tex]\[ t = 2 \][/tex]
[tex]\[ \frac{3t - 2}{4} - \frac{2t + 3}{3} = \frac{2}{3} - t \][/tex]
1. Eliminate the fractions by finding a common denominator, which in this case is 12 (the least common multiple of 4 and 3). Multiply every term by 12 to clear the fractions:
[tex]\[ 12 \left( \frac{3t - 2}{4} \right) - 12 \left( \frac{2t + 3}{3} \right) = 12 \left( \frac{2}{3} \right) - 12t \][/tex]
2. Simplify each term:
[tex]\[ 3t \cdot 3 - 2 \cdot 3 - 4 \cdot (2t + 3) = 4 \cdot 2 - 12t \][/tex]
[tex]\[ 9t - 6 - (8t + 12) = 8 - 12t \][/tex]
3. Distribute and Combine like terms:
[tex]\[ 9t - 6 - 8t - 12 = 8 - 12t \][/tex]
[tex]\[ t - 18 = 8 - 12t \][/tex]
4. Get all [tex]\( t \)[/tex]-terms on one side and the constants on the other side:
Add [tex]\( 12t \)[/tex] to both sides of the equation:
[tex]\[ t + 12t - 18 = 8 \][/tex]
Combine the [tex]\( t \)[/tex]-terms on the left-hand side:
[tex]\[ 13t - 18 = 8 \][/tex]
5. Solve for [tex]\( t \)[/tex]:
Add 18 to both sides:
[tex]\[ 13t = 26 \][/tex]
Divide both sides by 13:
[tex]\[ t = 2 \][/tex]
Thus, the solution to the equation is:
[tex]\[ t = 2 \][/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.